Pendidikan multikultural dalam program ”Catur Handayani” sebagai upaya penguatan wawasan kebangsaan Santri Pondok Pesantren Salafiyah Shirothul Fuqoha’ - Achmad Mufti Fauzi; Sri Untari (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Multicultural education is an extraordinary idea in the education system in Indonesia. The implementation of multicultural education can be carried out in Islamic boarding schools to strengthen student’s national insight. It is important due to the possibility intolerance among students who have various ethnic and cultural backgrounds. The research aimed to: (1) determined implementation of multicultural education in the “Catur Handayani” program, (2) described the driving and inhibiting factors for the implementation of multicultural education in the “Catur Handayani” program, (3) analysed the potential and perspectives of students regarding multicultural education in the “Catur Handayani” program. The research used study cased methods. The primary data source way interviews and observations The secondary data obtained from literature review and documentation. Data analysis includes data reduction, data display, verification, and credibility test. Multicultural education in the “Catur Handayani” programs has took from of a collaborative program between the Munadzomah Santri Shirothul Fuqoha’ organization and academics. The program as evidenced by the fact that students were experiencing positive behavioural changes. However, the density of Islamic boarding school activities was a limitation for multicultural education to achieve more significant results. This happens because the perspective of Islamic boarding school students tend to prioritized religious knowledge and then connect it with national insight. This research was proved that multicultural education applies in Islamic boarding schools and that the students have a unique perspective in viewing national insight in Indonesia.